Healthcare-associated Gram-negative bloodstream infections: antibiotic resistance and predictors of mortality - DURMUŞOĞLU, LÜTFİYE (W B SAUNDERS CO LTD, 2016)
This article describes the prevalence of antibiotic resistance and predictors of mortality for healthcare-associated (HA) Gram-negative bloodstream infections (GN-BSI). In total, 831 cases of HA GN-BSI from 17 intensive care units in different centres in Turkey were included; the all-cause mortality rate was 44%. Carbapenem resistance in Klebsiella pneumoniae was 38%, and the colistin resistance rate was 6%. Multi-variate analysis showed that age > 70 years [odds ratio (OR) 2, 95% confidence interval (CI) 1.22-3.51], central venous catheter use (OR 2.1, 95% CI 1.09-4.07), ventilator- associated pneumonia (OR 1.9, 95% CI 1.1-3.16), carbapenem resistance (OR 1.8, 95% CI 1.11-2.95) and APACHE II score (OR 1.1, 95% CI 1.07-1.13) were significantly associated with mortality. (C) 2016 The Healthcare Infection Society. Published by Elsevier Ltd. All rights reserved.
Keywords: Bloodstream; Gram-negative; Healthcare; KLEBSIELLA-PNEUMONIAE; OUTCOMES; IMPACT; ENTEROBACTERIACEAE; EPIDEMIOLOGY; SURVEILLANCE; BACTEREMIA; PROGRAM